Where Did They Come From? On Global Mobility of Chinese Returnees. Issue 1 (13th October 2021) - Peng, Yingzhen; Lou, Wen; He, Jiangen; Larivière, Vincent
Abstract: This study investigates the scientific mobility of Chinese returnees. Based on an analysis of scientific affiliation data in the Web of Science between 2008 to 2019, the paper explores the distribution of Chinese returnees from temporal and regional perspectives. The results confirm that there is an increasing number of Chinese migrant researchers who return home, and that mainly come back from developed countries.